Vincent van Gogh an explosion of colours. (Chicago distributed by Britannica Encyclopaedia Educational Corporation, 1989)
Based on the correspondence between van Gogh and his family and friends - especially his brother Theo van Gogh, a gallery owner - this program focuses on Vincent's final years.
Script and direction: Ludy Kessler ; produced by: Ludy Kessler and Rincovision Zurich ; producer: Wolfgang Frei.
Voice of van Gogh: Geoffrey Bateman ; narrators: Trevor Rowling, Robert W. Zanotti.
Keywords: Gogh, Vincent van -- 1853-1890.; Painters -- Netherlands -- Biography